Malnutrition in Acute Stroke: An Article Review - Lisda Amalia (Jurnal Neuroanestesi Indonesia)
The prevalence of malnutrition after stroke varies widely. It is estimated about one-fifth of patients with acute stroke are malnourished on initial hospital admission, while the prevalence of malnutrition ranges from 6.1 to 62%. Energy requirements increase due to stress caused by stroke, while food intake decreases due to impaired ability to eat, so the body will use its fat and protein stores as fuel to produce glucose. Muscle and fat tissue undergo degradation due to the breakdown of amino acids to form energy. Systemic consequences occur after stroke, peripheral immunodepression in association with overstimulation of the autonomic and neuroendocrine systems. Damage to cerebral tissue can activates the hypothalamus-pituitary-adrenal axis, resulting in increased levels of glucocorticoid hormones, catecholamines, and glucagon, leading to hypermetabolism (increased energy use), hypercatabolism (increased protein breakdown), and persistent hyperglycemia. The prevalence of malnutrition increases with the length of stay and decreased functional improvement during rehabilitation. Malnourished patients with stroke experience a higher stress reaction, which increases the occurrence of peptic ulcers, and infections of the respiratory and urinary tracts, thus extending the length of stay and increasing mortality